Associação de índices preditivos na avaliação do desmame da ventilação mecânica em pacientes com traumatismo cranioencefálico - Dias, Camila Marques (2014)
Evaluate the predictive capacity of associated index: airway occlusion pressure x respiratory rate/ tidal volume (P 0.1 x f/VT) regarding to weaning from mechanical ventilation (MV) in patients with traumatic brain injury (TBI).The associated index was measured after spontaneous breathing trials (SBT) for 30 minutes, ventilation mode with pressure support (PSV), 7 cmH2O of pressure support (PS) and positive end expiratory pressure (PEEP) of 5 cmH2O (PS above PEEP) and its accuracy and its components was evaluated using the area on the ROC curve (AUC). The f/VT index showed significance between the groups who were successful or unsuccessful weaning (p = .03), presenting moderate accuracy with AUC = 0.75 (p < .01). The P 0.1x f/VT index did not increase the accuracy of its components. There was no difference between the evaluated indexes with respect to type of artificial airway (AA) used. The evaluation of the predictive capacity demonstrated that f/VT obtained moderate accuracy and together with P 0.1 and its associated index can be used to evaluate the weaning of patients with TBI regardless of the AA, since there was no statistically significant difference between their accuracies.